(3eNJUQ UMjM eSdes - (3YHO GdYXje Hf YHO Gdbhj Hf YHO Gddg, CHh eMeO, Rcj GdOjf GdefPQj ,J (B656 (3g` s; (3GdGeGe eSde , CHh GdMSjf,J (B261 (3g` s ((3OGQ GdMOjK GdMGedjI s)
(3ChdgG (B:s
(3hHYO agPG cJGH GNJUQJg ef UMjM GdEeGe CHj GdMSf eSde GdfjSGHhQi QVi Gddg Yfg GNJUGQkG jSgdg Ydi MGaXjg s
(3BNQgG (B:s
(3bGd GdTjN Gdabjg GdEeGeRci GdOjf YHO GdYXje Hf YHO Gdbhi Hf YHO Gddg gPG BNQ eG GNJUQJg ef UMjM GdEeGe CHj GdMSjf eSde s
(3GdfSNI HgG MhGTs
(3HChdg eWGdYIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdMOjK h GdeUWdMs